Short-term outcomes of mini-sling versus transobturator tape in the surgical management of women with stress urinary incontinence. A randomized controlled trial - Ahmed Emam; Khaled Teama; Tarek Salem (Urogynaecologia International Journal, 2024)
The objective of this prospective randomized study was to assess the efficacy and safety of mini-sling in the management of female stress urinary incontinence (SUI) as compared to transobturator tape (TOT). A total of 42 female patients with SUI were included in this study. Patients were randomized into two equal groups, underwent either the TOT or the mini-sling procedure, and were followed up for 6 months. Compared to the TOT group, the mini-sling group had a statistically significant shorter operative time, less estimated blood loss, and a lower postoperative pain score. There was no statistically significant difference between both groups as regards postoperative fever, hospital stay, or vaginal erosion. The International Continence Index questionnaire showed a statistically significant improvement within each group after surgery, with the TOT group showing a statistically significant marginal improvement compared to the mini-sling group. Urodynamic testing showed no statistically significant difference between both groups regarding the first sensation of bladder filling, functional bladder capacity, maximal bladder capacity, postvoiding residual urine, and maximal flow rate. Both mini-slings and TOT were found to be safe and effective in treating female SUI with no clinically significant difference between both procedures.